Design of Efficient Partitioned Procedures for the Transient Solution of Aeroelastic Problems - Piperno, Serge; Farhat, Charbel (European Journal of Computational Mechanics, 2000)
We consider the problem of solving large-scale non-linear dynamic aeroelasticity problems in the time-domain using a fluid-structure partitioned procedure. We present a mathematical framework for assessing some important numerical properties of the chosen partitioned procedure, and predicting its performance for realistic applications. Our analysis framework is based on the estimation of the energy that is artificially introduced at the fluid-structure interface by the staggering process that is inherent to most partitioned solution methods. This framework provides a powerful means for the construction of more accurate and stable partitioned methods. Using two- and three-dimensional, transonic and supersonic, wing and panel aeroelastic applications, we validate this framework and highlight its impact on the design and selection of a staggering algorithm for the solution of coupled fluid-structure equations.